New Method of Treatment of Scarring Alopecia with Follicular Unit Hair Extraction Combined with Platelets Rich Plasma - J. Kadhum, Mohammad; Kadhim Al-Hattab, Mohammad; Hasan R. Al-Zurfi, Ahmed (Hammurabi Journal of Medical Sciences, 2025)
Background: Scarring alopecia (SCA) also known as cicatrical alopecia represents a group of disorders in which hair follicles are permanently destroyed and replaced with scar tissue and permanent hair loss. Objectives: To evaluate the effectiveness of follicular unit (FU) hair transplantation as a novel technique for the treatment of scarring alopecia compared with conventional surgical methods such as excision, local flap reconstruction, and tissue expansion. Materials and Methods: This study included patients with SCA of the scalp and beard area of different causes, was performed at private clinic in Al Najaf city from the 1st of January 2022 to the end of December 2023. The patients underwent a single session of hair transplantation combined with platelet rich plasma with number of graft range from 900 to 4800 grafts according to scar area. The results of patients with noticeable improvement in the photographs and patient satisfaction were recorded at 3&6 months after the procedure. Results: Fifteen patients were enrolled. Most of causes related to trauma, burn, surgical excision and tinea capitis .The hair growth started after three months and density of hair increase after six months. The patient and observer satisfaction significantly improved after the procedure, without significant side effect. Conclusions: FU hair transplantation could be an effective method for managing scar tissue and had several advantages, including a high transplantation survival rate and satisfactory postoperative results.